Computer Programs to Assist the Physician in the Analysis of Self-Monitored Blood Glucose Data - Berger, M. (1988)
We have developed new computer programs and algorithms to assist the physician in the analysis of data from patients with diabetes mellitus using “home monitoring of blood glucose”. These programs accept data from files created using a glucose meter equipped with memory and clock calender. The programs include: 1. “SUGAR3”, which has achieved the desired level of performance in terms of ease of use, speed, clarity and quality of graphical displays. This program is primarily for use in “batch” mode. 2. “MARK1”, which incorporates new methods and techniques for interactive analysis of the dynamics of glucose values obtained over a period of time covering up to several months together with their temporal relationships to type and dose of insulin and special user defined events. 3. “INSULIN”, which permits one to visualize the approximate profile of insulin action, for a regimen involving multiple injections or types of insulin.